1994
DOI: 10.1111/j.1365-2141.1994.tb04938.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of loss of a chromosome 17p and p53 gene mutations in blast crisis of chronic myelogenous leukaemia

Abstract: In 31 cases of chronic myelogenous leukaemia (CML) we examined the prognostic significance of chromosomal loss of a 17p and p53 mutations at the onset of blast crisis (BC). p53 mutations were closely related to a shortened survival in CML-BC (P< 0.005 by the logrank test), whereas loss of a 17p by itself was not a poor prognostic indicator. The prognostic significance of loss of a 17p, however, emerged when combined with its predominance in the metaphases analysed. This predominance might easily and rapidly be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 9 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…The BC stage of CML is commonly associated with nonrandom secondary chromosomal changes that, in addition to the t(9;22), include +Ph, +8, i(17q), +19, t(3;21)(q26;q22), and t(7;11)(p15;p15) (Prigogina et al,1978; Alimena et al,1987; Blick et al,1987; Melo et al,2003), or with mutations in the TP53, CDKN2A, RB1 , or RAS genes (Ahuja et al,1989; Kelman et al,1989; LeMaistre et al,1989; Feinstein et al,1991; Nakai et al,1992,1994; Mitani et al,1994; Nakai and Misawa,1995; Sill et al,1995; Nakamura et al,1996; Fioretos et al,1999; Beck et al,2000). However, the molecular mechanisms responsible for disease progression in CML have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The BC stage of CML is commonly associated with nonrandom secondary chromosomal changes that, in addition to the t(9;22), include +Ph, +8, i(17q), +19, t(3;21)(q26;q22), and t(7;11)(p15;p15) (Prigogina et al,1978; Alimena et al,1987; Blick et al,1987; Melo et al,2003), or with mutations in the TP53, CDKN2A, RB1 , or RAS genes (Ahuja et al,1989; Kelman et al,1989; LeMaistre et al,1989; Feinstein et al,1991; Nakai et al,1992,1994; Mitani et al,1994; Nakai and Misawa,1995; Sill et al,1995; Nakamura et al,1996; Fioretos et al,1999; Beck et al,2000). However, the molecular mechanisms responsible for disease progression in CML have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…BCR–ABL protein is known to confer apoptotic resistance to DNA damage (Bedi et al , 1995; Nishii et al , 1996; Amarante‐Mendez et al , 1998) and has also been shown to prolong cell cycle arrest at the G2M checkpoint via increased tyrosine phosphorylation of CDK1, which can be abrogated by caffeine treatment (Nishii et al , 1996). p53 loss of function is a common abnormality in the transition from chronic‐phase CML to blast crisis, and is associated with drug resistance, suppression of apoptosis and poor prognosis (Nakai et al , 1994; Stuppia et al , 1997).…”
mentioning
confidence: 99%
“…8 Inactivation of p53 plays an important role in neoplastic transformation in solid tumors and it has also been reported in hematological malignancies in association with progression of disease. [9][10][11][12] Most often loss of 17p is accompanied by a complex aberrant karyotype, which in principle results in a poor outcome. 5,6,[13][14][15][16] However, in some cases the p53 deletion is present as a single chromosomal aberration and as a consequence treated in the standard risk group.…”
Section: Introductionmentioning
confidence: 99%